Publisher Correction: Charging dynamics of an individual nanopore - Ran Tivony (Nature Communications, 2019)
The original version of this Article contained an error throughout in which an incorrect symbol was used for the diffusion coefficient: it should be cambria math, italicized, and not bold. These have been corrected in both the PDF and HTML versions of the Article.